(untitled) (Medical Forum Monthly, 2024)
Objective: To find out whether ingredients of hashish are helpful to treat anxiety, chronic pain, anorexia, insomnia and obesity. Study Design: Cross sectional questionnaire based study. Place and Duration of Study: This study was conducted in Karak City, KPK from March 2013 to march 2014. Materials and Methods: A cross sectional questionnaire based study was conducted in the Karak city. A sample of 100 hashish addicts was selected. They were asked questions about their routine use,dosage and behavior changes while using hashish. Their general behavior was observed and laboratory tests like LFT (ALT and total bilirubin) and RFT (Urea and creatinine) were done periodically. Results: It was noted that hashish addiction was more common in middle and lower class. Its use cause euphoria followed by 6 to 8 hours of sleep. Speech was coherent although they became more talkative. LFT’s and RFT’s were normal. Conclusion: Although hashish is a substance of addiction but it also has many positive effects and further research should be done to see if some of its ingredients could be used in treating anxiety, chronic pain, anorexia, insomnia, obesity and chronic depression.